Legal Protection of The Land Rights of The Wolio (Buton) Fort as a Cultural Heritage - La Ode Muhammad Iman Abdi Anantomo Uke (Al-'Adl, 2022)
Buton Fort is known as the largest fort in the world. For this reason, there is a need for legal protection for the Buton Palace Fort by the Government, especially the Baubau City government and the National Land Agency, in terms of Regulations and Efforts to Protect the Land Rights of the Buton Palace Fort as a cultural heritage. Because of these problems, protecting cultural heritage objects, including the land, is necessary. This research method is normative research that focuses on a legislative approach with primary data sources on the Basic Agrarian Law, the Cultural Heritage Act, and other laws and regulations such as the regional regulation on the particular area of Bau-bau City. The results of the study found fact that the land inside the fort of the Wolio Sultanate was land controlled by the people of the descendants of the bonto (sultanate officials/councils who elected the sultan) and Walaka (descendants of the sultan). However, the increase in population around the cultural heritage area can cause the displacement and destruction of cultural heritage objects. It can lead to a land sale and purchase agreement which is the land of Toerakia (usage rights). Referring to the Basic Agrarian Law, it is stated in the Fourth provision, namely the rights and authority over land and water from the autonomous or former autonomous regions that still existed at the time this Law came into force were abolished and transferred to the State. Based on this regulation, the regulation of the Wolio fort land should be transferred to the State.